Galium verum var. hallaensis, a replacement name for the Korean Galium pusillum Nakai (Rubiaceae) - Jeong, Keum Seon; Shin, Jae-Kwon; Jang, Kae Sun; Choi, Kyung (Phytotaxa, 2017)
Galium Linnaeus (1753: 105) is one of the largest genera within the family Rubiaceae and consists of approximately 650 species (Soza & Olmstead 2010), mostly annual and perennial herbaceous plants, mainly distributed in temperate regions. The genus is characterized by more than two leaf-like whorls, number of divided petal, rudimentary calyx and two locular ovaries (Ehrendorfer et al. 1994, 2014). Galium has serious problems for identification and taxon delimitation due to severe variations in the morphology of leaves, seed hairs and flowers. It is difficult to be correctly identified because the plants present a seasonal change in the morphology of vegetative parts (Soza & Olmstead, 2010).